2018
DOI: 10.1053/j.ajkd.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Results of ASERTAA, a Randomized Prospective Crossover Pharmacogenetic Study of Immediate-Release Versus Extended-Release Tacrolimus in African American Kidney Transplant Recipients

Abstract: Registered at ClinicalTrials.gov, with study number NCT01962922.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 58 publications
4
75
0
Order By: Relevance
“…In expressers, CYP3A5 comprises ~50% of all CYP enzymes . African Americans are more likely than whites to be CYP3A5*1 expressers (rates of 0.76‐0.85 vs 0.25, respectively), and African Americans therefore may require higher doses of tacrolimus to achieve therapeutic trough levels . Although differences in CYP expression are well described, the use of preemptive CYP genotyping has not been routinely implemented in transplant centers.…”
mentioning
confidence: 99%
“…In expressers, CYP3A5 comprises ~50% of all CYP enzymes . African Americans are more likely than whites to be CYP3A5*1 expressers (rates of 0.76‐0.85 vs 0.25, respectively), and African Americans therefore may require higher doses of tacrolimus to achieve therapeutic trough levels . Although differences in CYP expression are well described, the use of preemptive CYP genotyping has not been routinely implemented in transplant centers.…”
mentioning
confidence: 99%
“…CYP3A5*1 expressers demonstrate approximately 30% higher tacrolimus peak compared to nonexpressers to achieve comparable trough levels. This wide fluctuation and swing in tacrolimus pharmacokinetics may explain the higher incidence of DGF in CYP3A5*1 expressers compared to nonexpresser . Expectedly, any evaluation of the impact of tacrolimus on DGF should consider the day of tacrolimus initiation.…”
Section: Discussionmentioning
confidence: 99%
“…The main result of this study was that the genotype-guided TAC dose group increased the proportion of Thai KT patients with TAC [26][27][28] Further RCTs are needed to confirm an effect of the extended-release TAC formula on renal outcomes in different CYP3A5…”
Section: Discussionmentioning
confidence: 86%
“…An alternative approach is to either adjust the other immunosuppressive drugs so that high dose TAC could be avoided early in the time after transplantation or usage of other drugs, for example, diltiazem, that have interaction by decreasing TAC clearance resulting in the need for a lower TAC dosage. Additionally, recent studies demonstrated the distinct pharmacokinetics between extended‐release TAC and immediate‐release TAC formulas, therefore requiring different TAC doses in various CYP3A5 polymorphisms and ethnicities . Further RCTs are needed to confirm an effect of the extended‐release TAC formula on renal outcomes in different CYP3A5 genotypes.…”
Section: Discussionmentioning
confidence: 99%